FACTORS INFLUENCING INSECTICIDE-TREATED MOSQUITO NET UTILISATION AMONG PREGNANT WOMEN ATTENDING ANTE NATALCARE AT KAPCHORWA GENERAL HOSPITAL IN KAPCHORWA DISTRICT. A CROSS-SECTIONAL STUDY. - CHEMUTAI, PAUL; NEGESA, JUSTINE (Student's Journal of Health Research Africa, 2024)
Background The factors influencing utilization of insecticide-treated mosquito nets among pregnant women attending ANC at Kapchorwa General Hospital. Methodology A cross-sectional study of 100 respondents was used for the study. A simple random sampling technique was used and data collected using survey and interviewing methods was presented and analyzed using descriptive frequencies and percentages using Microsoft Excel and Microsoft Word. Results From the results, the majority 92(92%) of respondents said they knew about ITNs, the majority 58(58%) of respondents heard about ITNs from ANCs a majority 67(67%) said ITNs prevent malaria, a majority 89(89%) of respondents were willing to use ITNs, a majority 82(82%) were willing to recommend others to use ITNs, a majority 85(85%) said that sleeping under ITNs does not cause suffocation, a majority of married 92(92%) and high-income earners 65(74%), and mothers aged between 15 – 30 Years, 72(92%) were all utilizing ITNs. Conclusion From the results, the majority of respondents said that they knew about ITNs the majority of respondents heard about ITNs from ANC, and from the radio, the majority of respondents were willing to use ITNs, and a majority were willing to recommend others to use ITNs, majority of b married women were sleeping under ITNs, a majority of the individuals earning high income were sleeping under ITNs, and the majority of the mothers aged between 15 – 30 Years, were sleeping under ITNs. Recommendation Health workers and VHTs should encourage mothers to go to their nearest health facilities for antenatal visits, Health workers should health educate the mothers about the benefits of sleeping under ITNs to improve their attitude, Government should provide free ITNs to pregnant mothers to increase the utilization of ITNs.